Analisis Kualitas Isolasi Minyak Transformator 375 MVA dengan Interpretasi Rasio Roger, Segitiga Duval, Breakdown Test, dan Water Content Test - Abdul Syakur; Wildan Lazuardi (Diponegoro University, 2019)
Transformers is a vital instrument to distribute electricity from the power plant to the consumer. Therefore, it needs special maintenance to the performance of the transformer in order to avoid the damage. During the operation, the transformer oil will affect some thermal loading and electrical loading. Due to the load accumulation, it can cause dissolved hydrocarbon gases in oil that could potentially lead to a breakdown in the transformer. We need special monitoring against these gases. The other way to analyze the gas dissolved in oil is by using Dissolved Gas Analysis (DGA). The DGA will extract gases to know indications based on the interpretation of the data were performed. This method can also analyze the fault for a long term prediction, therefore the damage of the transformer can be prevented. The results of DGA analysis on the transformer is the Discharge of thermal fault obtained from data interpretation using Roger’s Ration and Duval’s Triangle method. In other way, the results of voltage breakdown testing indicate oil condition are still good that dielectric strength > 40 kv and for the water content measurement also has a good result at < 25 ppm.